Bicriteria scheduling on a series-batching machine to minimize maximum cost and makespan - He, Cheng; Lin, Hao; Lin, Yixun; Tian, Ji (Central European journal of operations research, 2013)
This paper studies the bicriteria problem of scheduling n jobs on a serial-batching machine to minimize maximum cost and makespan simultaneously. A serial-batching machine is a machine that can handle up to b jobs in a batch and jobs in a batch start and complete respectively at the same time and the processing time of a batch is equal to the sum of the processing times of jobs in the batch. When a new batch starts, a constant setup time s occurs. We confine ourselves to the unbounded model, where b ≥ n . We present a polynomial-time algorithm for finding all Pareto optimal solutions of this bicriteria scheduling problem.